2020
DOI: 10.1080/15592324.2020.1816321
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 edited HSFA6a and HSFA6b of Arabidopsis thaliana offers ABA and osmotic stress insensitivity by modulation of ROS homeostasis

Abstract: The role of Heat Shock Transcription Factor 6 (HSFA6a & HSFA6b) in response to abiotic stresses such as ABA, drought, salinity, drought, and osmotic stress is individually well established. Unfortunately, the functional redundancy between the HSFA6a and HSFA6b as well as the consequences of simultaneous editing of both in response to aforementioned stresses remains elusive. Therefore, this study was designed with the aim of addressing whether there is any functional redundancy between HSFA6a and HSFA6b as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…We found that SsKAI2 OEs promoted the expression level of ABA responsive genes, such as ABI3, ABI5, MYB96, MYB3R2, and ABF1 under cold stress (Figure 8), which is an agreement with the results of Li et al (2017) suggesting that KAI2 might regulate the abiotic stress tolerance could be ABA-dependent. The relationship of ABA with redox homeostasis is well documented in different studies Postiglione and Muday, 2020;Wenjing et al, 2020). Altogether, our results are suggesting that SsKAI2 enhanced response to ABA and induced expression level of ABA-responsive genes might be a pathway leading to redox homeostasis under cold stress.…”
Section: Karrikins Insensitive2 (Kai2supporting
confidence: 77%
“…We found that SsKAI2 OEs promoted the expression level of ABA responsive genes, such as ABI3, ABI5, MYB96, MYB3R2, and ABF1 under cold stress (Figure 8), which is an agreement with the results of Li et al (2017) suggesting that KAI2 might regulate the abiotic stress tolerance could be ABA-dependent. The relationship of ABA with redox homeostasis is well documented in different studies Postiglione and Muday, 2020;Wenjing et al, 2020). Altogether, our results are suggesting that SsKAI2 enhanced response to ABA and induced expression level of ABA-responsive genes might be a pathway leading to redox homeostasis under cold stress.…”
Section: Karrikins Insensitive2 (Kai2supporting
confidence: 77%
“…The genome editing method is a powerful technique for producing varieties; thus, several genome-edited plants are currently being produced [87,88]. Mutations in HSFA6a and HSFA6b, created by CRISPR/Cas9, are more tolerant to abiotic stresses such as ABA, mannitol, and sodium chloride [89]. Researchers have developed several mutants, such as the tomato ead1 mutant and soybean hsp90A2 mutant, using CRISPR/Cas9.…”
Section: Discussionmentioning
confidence: 99%
“…The orthologs of HSFA6b and HSFA6a are expressed in the primary and lateral roots of Arabidopsis (Hwang et al, 2014). HSFA6b also regulates root elongation in an ABA‐dependent manner (Wenjing et al, 2020) (Figure 3). ABA treatment or signalling is required for HSFA6a and HSFA6b expression and translocation to the nucleus.…”
Section: Phytohormones Regulation and Their Interactions In Roots Exp...mentioning
confidence: 99%
“…Wenjing et al, 2020) (Figure3). ABA treatment or signalling is required for HSFA6a and HSFA6b expression and translocation to the nucleus.…”
mentioning
confidence: 99%